Constructing Parenthood After Infertility: A Narrative Study of Adoptive Parents - Rodrigues da Silva, Diana; Okonkwo, Adaeze; Mwangi, Grace (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore how adoptive parents construct their identities and meaning of parenthood following experiences of infertility.Methods: This qualitative research employed a narrative methodology to investigate the lived experiences of 31 adoptive parents residing in Austria, all of whom had previously experienced infertility. Participants were recruited through purposive sampling, ensuring diversity in gender, relationship status, and duration since adoption. Data were collected through semi-structured interviews, each lasting between 60 and 90 minutes. Interviews were transcribed verbatim and analyzed using thematic narrative analysis with the assistance of NVivo software. Theoretical saturation guided the cessation of data collection. Data analysis focused on identifying shared themes and patterns in the way participants narrated their transition from infertility to adoptive parenthood.Findings: Three major themes emerged from the data: Redefining Parenthood, Emotional Journey, and Social and Relational Adjustments. Within these categories, participants described subthemes such as letting go of biological ties, reconstructing identity, symbolic rituals, emotional ambivalence, hope and renewal, navigating social stigma, and coping with institutional processes. Participants emphasized the importance of narrative reconstruction, spiritual or moral reframing, and peer support in legitimizing their parental identity. Despite the fulfillment found in adoption, many expressed that emotional residues from infertility persisted, shaping their experience of parenthood in both subtle and explicit ways.Conclusion: The findings highlight that adoptive parenthood after infertility is a complex, emotionally layered, and socially negotiated process. Narrative identity construction plays a vital role in helping individuals reconcile reproductive loss with the joys and challenges of adoption.